"I Can Learn How to Communicate Appropriately in This Language" Examining the Links between Language Mindsets and Understanding L2 Pragmatic Behaviours. Issue 3 (4th May 2022) - Zarrinabadi, Nourollah; Rezazadeh, Mohsen; Shirinbakhsh, Salva
ABSTRACT: Recent developments regarding mindsets have led to interesting findings in respect to language learning. Despite this interest, no one to the best of our knowledge has investigated individuals' mindsets regarding the learnability of second language (L2) pragmatic norms. This study was set out to explore the structural relation between L2 learners' belief systems -fixed and growth mindsets- and their L2 pragmatic norms including recognition, evaluation, perception, and conformity. Questionnaire data were collected from 213 learners of English as a foreign language in the context of Iran. The participants were asked to respond to questionnaire items on pragmatic norms, competence, motivation, and mindsets. Results of path analysis revealed that fixed and growth mindsets and L2 pragmatic competence positively predicted evaluation, perception and conformity to L2 pragmatic norms via the mediation of motivation. Our findings indicate that language mindsets play an important role in learners' motivation to learn and use the pragmatic norms of the language they are learning. Results also imply that growth mindset should be encouraged among both language teachers and learners in order to achieve better outcomes in teaching pragmatics.